Cuestiones criminales: ley y legalidades en la India precolonial y colonial - Dube, Saurabh; Rao, Anupama (El Colegio de México, 2014)
This essay and its sequel explore the relationship between crime and culture in order to better understand the changing terms, tactics, and textures of disciplinary authority, social control, and their several subversions in South Asia—from the eighteenth to the twenty-first centuries. Here, focusing on the pre-colonial and colonial periods, we seize upon crime as a point of entry not only to unravel the dynamic between states and subjects but to understand as well the ways in which intimate social lives have been shaped by these encounters. We argue that crime is at once a category produced by legal regimes and governmental registers as well as a practice intimating the intersections of social experience and state power. At stake, then, are multiple articulations between authoritative categories, formations of state authority, and structures of everyday life. These articulations themselves suggest that far from constituting a settled fact, questions of crime are better approached as problems of knowledge and of knowing.